(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
This paper describes several chambered hexactinellid sponges, including Casearia iranica n.sp., C. vezvanensis n. sp., C. delijanensis n. sp., Esfahanella magna gen. n. n. sp., and E. parva gen. n. n. sp. from reefs of the Upper Triassic (Norian-Rhaetian) Nayband Formation exposed south of the town of Delijan in central Iran. The relative abundance of chambered and non-chambered hexactinellid sponges at this locality - as compared to hypercalcified representatives - highlight the importance of this group of sponges in reef and reefal limestones in central and east Tethys (China, Caucasia, Iran).